Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1109/tit.2019.2961323
|View full text |Cite
|
Sign up to set email alerts
|

Capacity Scaling of Massive MIMO in Strong Spatial Correlation Regimes

Abstract: This paper investigates the capacity scaling of multicell massive MIMO systems in the presence of spatially correlated fading. In particular, we focus on the strong spatial correlation regimes where the covariance matrix of each user channel vector has a rank that scales sublinearly with the number of base station antennas, as the latter grows to infinity. We also consider the case where the covariance eigenvectors corresponding to the non-zero eigenvalues span randomly selected subspaces. For this channel mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 59 publications
(225 reference statements)
0
15
0
Order By: Relevance
“…Since the noise power per antenna is normalized, P ul can be regarded as the transmit SNR per user, and SNR denotes the normalized transmit SNR per cell. Although we only describe the uplink MIMO, main results in this work are extended to the downlink [11].…”
Section: C(snr)mentioning
confidence: 99%
See 3 more Smart Citations
“…Since the noise power per antenna is normalized, P ul can be regarded as the transmit SNR per user, and SNR denotes the normalized transmit SNR per cell. Although we only describe the uplink MIMO, main results in this work are extended to the downlink [11].…”
Section: C(snr)mentioning
confidence: 99%
“…where the definitions of T T T k and T T T k can be found in [11]. A proof of the second term caused by pilot contamination in the denominator of (9) is particularly given in Appendix.…”
Section: A Coherent Lower Boundmentioning
confidence: 99%
See 2 more Smart Citations
“…In stark contrast, a different set of investigations has shown that correlation can enhance MU-MIMO performance [11][12][13][14][15][16][17][18][19][20]. Collectively, a critical observation from these studies is that the departing spread of electromagnetic energy from the BS can arrive at the terminals with substantially different power angular spectra, leading to variations in the channel statistics.…”
Section: Introductionmentioning
confidence: 99%